Product Defect Evaluation in Manufacturing Using Six Sigma Approach: Evaluasi Cacat Produk dalam Manufaktur Menggunakan Pendekatan Six Sigma - Harahap, Moch. Rizwan Riandi; Sulistiyowati, Wiwik (Indonesian Journal of Innovation Studies, 2025)
General Background Quality control is essential in manufacturing systems to maintain product consistency and minimize defects. Specific Background Production processes often experience defects that reduce quality performance and increase operational inefficiencies. Knowledge Gap Previous studies have applied quality control methods separately, with limited integration of Six Sigma and Failure Mode and Effects Analysis (FMEA) for comprehensive defect evaluation. Aims This study aims to identify dominant defects, analyze root causes, and determine priority corrective actions in a manufacturing process. Results The findings reveal that several defect types dominate production, with sigma level indicating the need for improvement. Root causes are identified through systematic analysis, while FMEA determines priority risks based on Risk Priority Number values. Novelty This study integrates multiple quality control tools in a structured framework for defect evaluation. Implications The results provide guidance for improving production processes and reducing defect rates in manufacturing systems. Keywords: Quality Control, Product Defects, Six Sigma, FMEA, Manufacturing Key Findings Highlights Dominant defect types identified in production process Risk ranking highlights critical failure priorities Integrated analysis supports structured decision making